2014
DOI: 10.1155/2014/378908
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Screening for Latent TB Infection prior to Biologic Therapy to Improve Patient Safety and Reduce Costs: A Prospective Observational Study

Abstract: Objective. Our current practice of screening for latent TB infection (LTBI) using universal T-SPOT assays is not in line with British Thoracic Society (BTS) recommendations. We set out to determine the clinical benefit and cost effectiveness of blanket TSPOT.TB (T-SPOT) testing as a screening tool for patients awaiting anti-TNF-α therapy. Methods. 130 consecutive rheumatology patients were investigated for LTBI before commencing anti-TNFα therapy at Gartnavel General Hospital, Glasgow, an area of low TB preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The activation of indolent TB during immunosuppressive therapy has received much emphasis in the western literature 7,8 but has always been a cause for concern in India. It is important to have a high degree of suspicion of the possibility of re-activation of TB during heavy immunosuppressive therapy especially in steroid resistant disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of indolent TB during immunosuppressive therapy has received much emphasis in the western literature 7,8 but has always been a cause for concern in India. It is important to have a high degree of suspicion of the possibility of re-activation of TB during heavy immunosuppressive therapy especially in steroid resistant disease.…”
Section: Discussionmentioning
confidence: 99%
“…The two main available tests are the tuberculin skin test (TST) and interferon-γ release assays (IGRAs). Though TST shows high sensitivity in individuals with normal immune responses 12 the sensitivity in people with previous Bacille Calmette-Guérin (BCG) vaccination, prior exposure to nontuberculous mycobacteria and immunosuppressant medication is lower 7 . Though some studies suggest the T-SPOT blood test which is a type of IGRA to diagnose latent TB 7,13 , a study by Ratnatunga et al in Sri Lanka showed no advantage in using T-SPOT.TB over TST 14 .…”
Section: Discussionmentioning
confidence: 99%